What the signs say : language, gentrification, and place-making in Brooklyn - Trinch, Shonna L.; Snajdr, Edward (Vanderbilt University Press, 2020)
"Argues that the public language of storefronts is a key component to the creation of place in Brooklyn, New York. Uses a sample of more than 2,000 storefronts and over a decade of ethnographic observation and interviews to charts two types of local Brooklyn retail signage: Old School, which uses many words, large lettering, and repetition, and New School, with hallmarks of brevity and wordplay. Presents in-depth ethnographic case studies that reveal how gentrification and corporate redevelopment in Brooklyn are connected to public communication, literacy practices, the transformation of motherhood and gender roles, notions of historical preservation, urban planning, and systems of privilege"--